2012
DOI: 10.1002/ar.22522
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Secondary Follicle Cycle of Hexi Cashmere Goat

Abstract: This experiment conducted to identify a periodic change of ultrastructures of secondary follicle characteristics during a whole year, reveal the molecule regulation of growth of cashmere. A total of 10 cashmere goats of 1-year old were studied. The paraffin section and ultrathin slices of skin were made each month in a whole year, observed, photographed, and analyzed under light microscope and transmission electron microscope after stained. Following the development of down fiber, the ultrastructures of second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Henderson and Sabine () argued that the new SF came out beside the old SF. We affirmed their results under TEM (He et al, ). Researchers (Li et al, ) found that new SF firstly grows in group, and then separated into individual SF.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Henderson and Sabine () argued that the new SF came out beside the old SF. We affirmed their results under TEM (He et al, ). Researchers (Li et al, ) found that new SF firstly grows in group, and then separated into individual SF.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, a better comprehension of skin biology and the factors that control the density and activity of follicle is required to breed the excellent species. We have reported that there were five different periods during a down fiber cycle and confirmed the specific time the five stages presented (He et al, ).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Cashmere is produced by secondary follicles (SF) in the skin of goats, and fiber production has been described in New Zealand cashmere goats, Liaoning cashmere goats, Mongolian cashmere goats, Iranian cashmere goats, Spanish cashmere goats, Gray goats and Hexi cashmere goats (Nixon et al, ; Li et al, ; Li et al, ; Ansari‐Renani et al, 2010a; Ansari‐Renani et al, 2010b; Wang et al, ; Dong et al, ; He et al, a,b). The SF show a periodic growth pattern, with defined periods called anagen, catagen, and telogen.…”
mentioning
confidence: 99%
“…Hair follicles enter the anagen and begin to grow rapidly. After entering the catagen phase, the hair balls begin to atrophy and become thinner, and gradually move upward; the hair follicles entering the telogen are only above the sebaceous glands, and the cells are in a static state ( 5 ). The periodic growth of cashmere goat hair follicles is regulated by a series of molecules, including hormone regulation, such as melatonin ( 6 ), prolactin ( 7 ), thyroxine ( 8 ), and so on.…”
Section: Introductionmentioning
confidence: 99%